2022
DOI: 10.3897/rrpharmacology.8.80376
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction: developmental mechanisms and therapeutic strategies

Abstract: Introduction: Every year the importance of the normal functioning of the endothelial layer of the vascular wall in maintaining the health of the body becomes more and more obvious. The physiological role of the endothelium: The endothelium is a metabolically active organ actively involved in the regulation of hemostasis, modulation of inflammation, maintenance of hemovascular homeostasis, regulation of angiogenesis, vascular tone, and permeability. Risk factors for the development of endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 284 publications
(238 reference statements)
0
1
0
1
Order By: Relevance
“…The deficiency of isoleucine and leucine, in turn, was reflected in the loss of muscle mass, as it has been proved that it has an important role in obtaining energy from muscle glycogen, and its deficiency led to the manifestation of hypoglycemia (Anastasilakis et al 2022;Gandylyan et al 2023). The identified arginine deficiency contributed to endothelial dysfunction in vascular wall function (Shcheblykin et al 2022). A number of morphological studies revealed significant lipid deposits in the arterial intima, which was clinically manifested by increased blood viscosity with signs of progressively developing atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…The deficiency of isoleucine and leucine, in turn, was reflected in the loss of muscle mass, as it has been proved that it has an important role in obtaining energy from muscle glycogen, and its deficiency led to the manifestation of hypoglycemia (Anastasilakis et al 2022;Gandylyan et al 2023). The identified arginine deficiency contributed to endothelial dysfunction in vascular wall function (Shcheblykin et al 2022). A number of morphological studies revealed significant lipid deposits in the arterial intima, which was clinically manifested by increased blood viscosity with signs of progressively developing atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…Изучение фармакологической активности селективного ингибитора аргиназы-2 и тромбина из группы соединений фенольной природы с лабораторным шифром КУД975 на модели артериальной легочной гипертензии, индуцированной гипоксией. [21,22].…”
Section: цельunclassified